Improving the service time of web clients using server redirection. - Ardaiz, Oscar (Sigmetrics :performance evaluation review.)
This paper describes and evaluates experimentally a web server infrastructure, which consists of a small number of servers that redirect client requests based on the estimated client service time. The web servers have replicated content, are located in geographically different regions, and redirect clients between servers. The web servers use metrics obtained from server logs to estimate the service time of a client. Based on the estimated service time the server redirects the web client. The implementation of the measurement and redirection mechanism is done in the web servers and is independent of the clients. Using server logs the measuring mechanism does not introduce traffic into the network. We have experimentally evaluated the proposed web server infrastructure. In our experiments the client service time improved from 4 to 40 % when using the proposed mechanism. The web server infrastructure could be applied to improve the service time of selected clients, which frequently access a web server to retrieve a significant amount of data.